Potentiels et limites des traces (géo)numériques dans l’analyse des mobilités : l’exemple des données de la plateforme de covoiturage BlaBlaCar - Boris Mericskay (Cybergeo, 2019)
Big data is a field of investigation rich in promises but still complex in renewing spatial mobility analysis. In fact, thinking about mobility through the prism of digital footprints raises many questions regarding the data nature, the accessibility procedures and the methods and techniques of treatment. This paper aims to explore the potential of digital footprints in the analysis of mobility through the example of data from the Carpooling platform BlaBlaCar. By analyzing (temporal and spatial) trips to and from city of Rennes over the course of 5 months, the goal is both to draw a portrait of Carpooling in the capital of Britanny and to give an overview of advantages and limitations of these data in understanding this new form of mobility.